Investigation of the effectiveness of ECOLAB 'Drape ArmourTM' Radiation Protection in limiting eye-lens doses of healthcare personnel exposed to ionizing radiation during gastroenterology - interventional radiology procedures - Fulvio IM Fucilli; Giuseppe Di Giovanni; Alessandro Mastrorocco; Matteo Ninni; Piero Loprete; Isa De Crudis; Massimiliano Marano; Antonio Santomauro; Fabio Fucilli (Global Journal of Cancer Therapy - Peertechz Publications, 2022)
Objectives: To investigate the efficiency of the ECOLAB "Drape ArmourTM" device in limiting the eye-lens doses absorbed by healthcare personnel exposed to ionizing radiation, in a four-month trial during gastroenterology interventional radiology procedures.  Methods: Eyelens doses measured with eye-lens dosimeters calibrated in terms of equivalent dose at 3 mm depth ( Hp(3) ) were collected and analyzed since 2016 along with the irradiation parameters (Dose Area Product - DAP).  The eye-lens doses received during the four-month trial, have been compared with doses normally received, in the same conditions of irradiation, in the absence of the protection drape. Results: During the period of use of Drape ArmourTM, the average dose to the eye lens was estimated to be 0.73 mSv (St.dev = 0.40 mSv). The average dose to the eye lens, measured in the same four-month period, across different years from 2017 to 2021, was equal to 1.30 mSv (st. dev = 0.35 mSv). Conclusions: Results suggest the effectiveness of Drape ArmourTM in containing the doses to the eye lens. Keypoint: Limiting eye-lens doses to a maximum value of 20 mSv/year is a real challenge, especially in interventional radiologic facilities. The use of suitable radio-opaque drapes may help healthcare workers involved in such facilities. The aim of the work is to evaluate the efficiency of the ECOLAB "Drape ArmourTM" sterile mono-use drape.